Distinct roles for BAI1 and TIM-4 in the engulfment of dying neurons by microglia - Mazaheri, Fargol; Haas, Petra; Wittbrodt, Joachim (Nature Communications, 2014)
The removal of dying neurons by microglia plays a key role in both vertebrate nervous system development and several diseases. Here, the authors use a quantitative live imaging approach to investigate neuronal-microglial interactions at single-cell resolution and establish the functions of the phosphatidylserine receptors, TIM-4 and BAI1, in neuronal engulfment.
Gesehen am 08.02.2017